2004
DOI: 10.1016/j.jcrs.2004.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraocular lenses on preventing posterior capsule opacification

Abstract: There was no substantial difference in PCO prevention between IOLs with sharp posterior optic edges, regardless of the IOL's material composition. The anterior edge design appeared to have no preventive effect. These results confirm that a sharp posterior optic edge is the main factor in preventing PCO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 15 publications
0
101
0
4
Order By: Relevance
“…As there is little posterior pressure in eyes with no vitreous, and capsular bend formation may require not only a sharp optic edge but also posterior pressure, it is possible that the IOL edge has a minimal effect in reducing PCO in phacovitrectomy. 18 Also, more postoperative inflammation probably leads to lens epithelial cell migration and more extensive PCO in the phacovitrectomy. 5 On the other hand, Inoue et al 19 reported that a 25-gauge vitrectomy group had significantly less postoperative ocular inflammation than a 20-or a 23-gauge vitrectomy group in rabbit eyes.…”
Section: Resultsmentioning
confidence: 99%
“…As there is little posterior pressure in eyes with no vitreous, and capsular bend formation may require not only a sharp optic edge but also posterior pressure, it is possible that the IOL edge has a minimal effect in reducing PCO in phacovitrectomy. 18 Also, more postoperative inflammation probably leads to lens epithelial cell migration and more extensive PCO in the phacovitrectomy. 5 On the other hand, Inoue et al 19 reported that a 25-gauge vitrectomy group had significantly less postoperative ocular inflammation than a 20-or a 23-gauge vitrectomy group in rabbit eyes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, because of little posterior pressure in eyes with no vitreous, it is possible that the IOL edge effect which reduces PCO is minimal in a combined or a sequential surgery [27]. Thus, increase of PCO rate may be anticipated in the combined or the sequential surgery rather than in CS alone.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in mean uncorrected and best-corrected visual acuity reported at 15 months was due to posterior capsular opacification which improved significantly after YAG capsulotomy. 10 Anterior and posterior capsule opacifications are frequent complications of foldable IOL implantation and are related to factors such as IOL material, its design, 11 and surgical technique. 12 Auffarth et al 13 reported the rate of Nd : YAG laser capsulotomy over 3-year follow-up period to be (7.1%) in the hydrophobic acrylic group, followed by silicone (16.2%), PMMA (19.3%) and hydrophilic acrylic (31.1%), respectively.…”
Section: Evolution Of Microincision Cataract Surgerymentioning
confidence: 99%